Evaluation of long-term memory through electroencephalographic techniques (Research, Society and Development, 2023)
This study aimed to evaluate the long term memory through electroencephalographic techniques. Were evaluated, in individuals from the human and exact sciences groups, during the following cognitive activities: task: 1 – MEMORIZING WORDS; 2 – REMEMBER THE WORDS OF ACTIVITY 1; 3 – MEMORIZING FIGURES; 4 REMEMBER THE FIGURES OF THE ACTIVITY 3. The gamma rhythm was recorded through the electroencephalogram (EEG), according to the 10-20 system. Thus, the tasks aimed to analyze the capacity for long-term memorization. EEG signals were monitored during the reading and response of the tasks and the means and standard deviation of the gamma rhythm were calculated. The statistical model was BioEstat 5.0, T test for paired samples (p